Electrochemical Monitoring of ROS/RNS Homeostasis Within Individual Phagolysosomes Inside Single Macrophages. Issue 23 (2nd May 2019) - Zhang, Xin‐Wei; Oleinick, Alexander; Jiang, Hong; Liao, Quan‐Lan; Qiu, Quan‐Fa; Svir, Irina; Liu, Yan‐Ling; Amatore, Christian; Huang, Wei‐Hua
Abstract: The existence of a homeostatic mechanism regulating reactive oxygen/nitrogen species (ROS/RNS) amounts inside phagolysosomes has been invoked to account for the efficiency of this process but could not be unambiguously documented. Now, intracellular electrochemical analysis with platinized nanowire electrodes (Pt‐NWEs) allowed monitoring ROS/RNS effluxes with sub‐millisecond resolution from individual phagolysosomes impacting onto the electrode inserted inside a living macrophage. This shows for the first time that the consumption of ROS/RNS by their oxidation at the nanoelectrode surface stimulates the production of significant ROS/RNS amounts inside phagolysosomes. These results establish the existence of the long‐postulated ROS/RNS homeostasis and allows its kinetics and efficiency to be quantified. ROS/RNS concentrations may then be maintained at sufficiently high levels for sustaining proper pathogen digestion rates without endangering the macrophage internal structures. Abstract : Single nanowire electrode amperometry was used to establish that the consumption of ROS/RNS in a phagolysosome leads to a ROS/RNS production. This validates the long‐sought ROS/RNS homeostatic mechanism that was hypothesized to regulate the ROS/RNS intravesicular content during pathogens digestion.